Effective lagrangian for a mass dimension one fermionic field in curved spacetime - Bueno Rogerio, R. J. [UNESP]; Hoff da Silva, J. M. [UNESP]; Dias, M.; Pereira, S. H. [UNESP] (Springer Nature, 2018)
In this work we use momentum-space techniques to evaluate the propagator G(x, x′) for a spin 1/2 mass dimension one spinor field on a curved Friedmann-Robertson-Walker spacetime. As a consequence, we built the one-loop correction to the effective lagrangian in the coincidence limit. Going further we compute the effective lagrangian in the finite temperature regime. We arrive at interesting cosmological consequences, as time-dependent cosmological ‘constant’, fully explaining the functional form of previous cosmological models.
Keywords: Cosmology of Theories beyond the SM; Effective Field Theories; Thermal Field Theory